Linking Equal Employment Opportunity to Innovative Work Behavior: The Roles of Organizational Justice, Psychological Safety, and Employee Engagement - Venesia Venesia; Syarifah Novieyana; Maria Christiana Iman Kalis (LPPM STIE Kasih Bangsa, 2026)
This study explored the impact of equal employment opportunity (EEO) on innovative work behavior, with organizational justice, psychological safety, and employee engagement as mediators, within Indonesia's banking sector. A quantitative survey design was used, gathering data from employees in both private and state-owned banks. Partial least squares structural equation modeling (PLS-SEM) was applied to analyze the proposed relationships. The findings indicated that EEO positively influenced perceptions of fairness, interpersonal safety, and work engagement. These psychological factors were found to have a positive impact on innovative work behavior. Additionally, all three variables acted as significant mediators between EEO and innovative behavior. In essence, the study highlighted how EEO policies based on fairness helped create a work environment that promotes engagement and psychological safety, thereby encouraging employees to generate new ideas and contribute to organizational improvements. These results emphasize the role of fair human resource practices in fostering innovation within organizations.